2017
DOI: 10.1002/2017ms001092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of WRF SCM Simulations of Stratocumulus‐Topped Marine and Coastal Boundary Layers and Improvements to Turbulence and Entrainment Parameterizations

Abstract: Stratocumulus‐topped boundary layers (STBLs) are notoriously difficult to parameterize in single‐column models due to the strong inversion layer across which entrainment mixing plays an important role in modulating the boundary layer mass, energy, and moisture balances. We compare three different WRF planetary boundary layer (PBL) schemes (Yonsei University, YSU; Asymmetric Convective Model version 2, ACM2; Mellor‐Yamada‐Nakanishi‐Niino, MYNN) against large eddy simulations (LES) to find out that they underest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 38 publications
(73 reference statements)
0
27
0
Order By: Relevance
“…used the conserved ice-liquid-water potential temperature θ il to revise the identification of the PBL height in the new option, and Ghonima et al (2017) confirmed that this approach leads to a significantly improved simulation. For a fair comparison with Exp-TOP, the same method of the PBL height calculation is adopted in Exp-noTOP as well.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 80%
See 2 more Smart Citations
“…used the conserved ice-liquid-water potential temperature θ il to revise the identification of the PBL height in the new option, and Ghonima et al (2017) confirmed that this approach leads to a significantly improved simulation. For a fair comparison with Exp-TOP, the same method of the PBL height calculation is adopted in Exp-noTOP as well.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 80%
“…To explore the impact of the top‐driven diffusion on the sea fog simulation, two experiments with and without the option of ysu_topdown_pblmix, Exp‐TOP and Exp‐noTOP, are conducted. Wilson and Fovell () used the conserved ice‐liquid‐water potential temperature θ il to revise the identification of the PBL height in the new option, and Ghonima et al () confirmed that this approach leads to a significantly improved simulation. For a fair comparison with Exp‐TOP, the same method of the PBL height calculation is adopted in Exp‐noTOP as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global NWP models (e.g., Teixeira 1999) and climate models tend to underestimate Sc clouds (Teixeira et al 2011;Lin et al 2014), although there is an improvement in the representation of the radiative properties by a newer generation of climate models (Engström et al 2014). In terms of mesoscale models, Ghonima et al (2017) compared three different PBL schemes in the Weather Research and Forecasting (WRF) Model and found that they all underestimate entrainment, producing too moist and cold STBLs. Huang et al (2013) compared five different WRF PBL parameterizations and highlighted the difficulties of simulating the STBL.…”
Section: Introductionmentioning
confidence: 99%
“…All of these contribute to improvements in our ability to predict fog. Here, we present a reexamination of the relationship between LWC and visibility, motivated primarily by the fact that the WRF model has shown a moist bias in recent studies (Banks et al, ; García‐Díez et al, 2013; Ghonima et al, ). This previously observed overestimate in water may cause the higher liquid water and water vapor in our simulations, which would explain the negative bias in the visibility predicted by the Kunkel equation.…”
Section: The Extinction Coefficient and Visibilitymentioning
confidence: 99%